Coffee, tea, and chocolate consuming the world - You, Yao-Fen (Detroit Institute of Arts, 2016)
"This catalogue was published in conjunction with the exhibition Bitter/Sweet: Coffee, tea, and chocolate, at the Detroit Institute of Arts, November 20, 2016 - March 5, 2017"